Crystallization and preliminary structural characterization of the two actin-depolymerization factors of the malaria parasite - Huttu, Jani; Singh, Bishal Kumar; Bhargav, Saligram Prabhakar; Sattler, Julia M.; Schüler, Herwig; Kursula, Inari (Acta crystallographica. Section F, Structural biology communications, 2010)
The malaria parasite Plasmodium depends on its actin-based motor system for motility and host-cell invasion. Actin-depolymerization factors are important regulatory proteins that affect the rate of actin turnover. Plasmodium has two actin-depolymerization factors which seem to have different functions and display low sequence homology to the higher eukaryotic family members. Plasmodium actin-depolymerization factors 1 and 2 have been crystallized. The crystals diffracted X-rays to maximum resolutions of 2.0 and 2.1 Å and belonged to space groups P3121 or P3221, with unit-cell parameters a = b = 68.8, c = 76.0 Å, and P21212, with unit-cell parameters a = 111.6, b = 57.9, c = 40.5 Å, respectively, indicating the presence of one or two molecules per asymmetric unit in both cases.
Gesehen am 02.06.2023